Strategi Pemerintah Kota Subulussalam Dalam Meningkatkan Kesejahteraan Petani Sawit - Havida Zein; Nurhaslita Sari (UIR Press, 2022)
This study discusses how the Subulussalam city government’s strategy in improving the wel fare of oil palm farmers, with qualitative research methods that emphasize a descriptive approach,the study aims to examine whether the Subulussalam city government is trying or not in improving welfare and how the condition of farmers is in the situation of fluctuating FFB prices and then what obstacles are faced by the goverment in improving the welfare of oil palm farmers in Subulussalam city. And the results of the study indicate that the Subulussalam City Government has established policies that seek to improve the welfare of oil palm farmers in the city of Subulussalam which is currently still in a low state and needs to be improved further, while some of the policy efforts provided by the Subulussalam city government are the empowerment of farmers/planters, the program is the formation of farmer groups as a forum that accommodates various aspirations from farmers, developing human resources for oil palm farmers where the program is counseling guidance on good and right gardening, while the next effort is to increase the production of oil palm plantations as stated in the PSR program and efforts to provide facilities and infrastructure There are also several programs, namely the opening of production roads, distribution of oil palm seeds, procurement of subsidized fertilizers and other efforts to stabilize FFB prices. Subulussalam City has tried to improve the welfare of oil palm farmers in various ways.